THE ANALYSIS OF POOR COMMUNICATION IMPACT ON STUDENTS’ INTEREST IN LEARNING EXPONENT TOPIC - Almardhiyyah, Al Ainaa; Sulistyowati, Fitria; Kuncoro, Krida Singgih; Nugraheni, Zahra; Hapsari, Nadya Amalia Putri (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
Classroom learning requires effective communication between teachers and students to create a conducive environment and enhance learning. This study analyzes the impact of teacher communication on students' interest in learning exponents using a descriptive approach. Data were collected through observation, interviews, and documentation involving 10th-grade students and a mathematics teacher at a vocational school in Yogyakarta, selected via purposive sampling. The findings show that effective communication increases students' motivation, active participation, and understanding of exponents. Interactive methods, such as discussions and QA sessions, foster student engagement and improve their grasp of the material. These results highlight the critical role of teacher-student communication in creating an enjoyable and effective learning experience, ultimately supporting better academic outcomes.